Product form innovation: a morphodynamic factors-driven approach. (4th February 2022) - Zhang, Zhipeng; Su, Jianning; Li, Xiong; Yang, Wenjin
In this paper, a morphological dynamics factors-driven product form concept design method is proposed. The approach is based on three modules: analysis and capture of the set of product morphological dynamics factors, morphological algorithm design and computation, and morphological optimisation. The proposed approach has two advantages: linking the dynamic factors to uncertainty perception and using parametric modellers to improve the adaptability of the modelling schemes through the continuous interaction of knowledge between designers, users, and engineers; and the configuration of external parameters in terms of representational behaviours. The modeller is constructed with adaptive and fast response features to quickly obtain 3D product form solutions by inputting different 2D sketch features to the program. This study demonstrated the effectiveness of the method through a case study of helmet morphology design.